Comminuted Trapezium Fracture: Case Presentation and Review of Surgical Fixation Techniques. (28th May 2021) - Spielman, Amanda F.; Sankaranarayanan, Sriram
Abstract : We report a case of a 28-year-old male who sustained a comminuted trapezium fracture with carpometacarpal subluxation of the right hand. Treatment with internal fixation with a headless compression screw resulted in excellent outcomes.